Prices and Profits in State Enterprise - Henderson, A. M. (Review of Economic Studies, 1948)
Journal Article Prices and Profits in State Enterprise Get access A. M. Henderson A. M. Henderson Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 1, 1948, Pages 13–24, https://doi.org/10.2307/2296140 Published: 01 April 1948